Prosecuting controlling or coercive behaviour in England and Wales: Media reports of a novel offence - McGorrery, Paul (Criminology & criminal justice, 2021)
The offence of controlling or coercive behaviour came into effect in England and Wales in December 2015, and related offences have since been enacted in Scotland and Ireland. To date, there has been almost no empirical evaluation of the operationalisation of the new English and Welsh offence. This article fills that gap by analysing media reports relating to 107 individuals convicted of controlling or coercive behaviour, providing a profile of offenders and victims (gender and age), the types of abusive behaviours offenders engaged in and how the cases progressed through the criminal justice system (manner of conviction, sentencing outcomes). Media reporting of these cases is also discussed. The results suggest that the offence is (appropriately) operationalised in a highly gendered manner, that it has captured a diverse range of behaviours that would not previously have been considered criminal, and that media reports of this form of domestic violence have not demonstrated the negativity towards victims identified in previous studies. Further research of primary data is required to confirm these findings.